Perfil Constitucional da Educação Superior no Brasil: Aspectos históricos e atuais - Macedo, Caio Sperandéo de (2005)
It is appropriate to clarify that, in view of the topic chosen for this masters dissertation, namely Constitutional Profile of Higher Education in Brazil: Historical and Current Aspects , it was decided to adopt as the proper methodology an evaluation of what is understood nowadays by Education, the distinction between it and the terms instruction and teaching, as well as its legal nature. Next, discuss the importance and acknowledgement of the right to education in international treaties ratified by Brazil or to which it has been a party. As well, we will comment upon the immediate applicability of the norms defining fundamental rights and guarantees such as Education; including Education, as a fundamental social right, in the roll of immutable clauses . We will provide an overview of Education, as well as Higher Education, commenting upon the main legal measures relating to the topic in our seven Constitutions: The Imperial Letter of 1824; the Constitution of 1891; the Constitution of 1934; the Constitution of 1937; the Constitution of 1946; Constitution of 1967; and the current Constitution of 1988. Then, also comment upon current aspects under discussion in the field of Higher Education, notably the Autonomy of Universities; recalling the experience of autonomy of the São Paulo Universities (USP, Unesp and Unicamp); the danger of curtailing its full exercise; and emphasize that autonomy of universities consecrated in the Constitution of 1988 makes it possible to develop an important share of the social responsibility of educational institutions. In ending, set out the conclusion of the analysis, defending the Welfare State as policy, deploying our Constitutional Educational framework, promoting effective access to Education by the population and chiefly Higher Education, the latter combined with the necessary autonomy and inherent attributes of universities, as a vital contribution to the country s project for socioeconomic development, sealing the social pact advocated by the foundational precepts and objectives of our Republic